Design of Pedal Bicycle Prototype using the PID Controller as an Alternative Energy Generator - Rizanty, Reyhan; Wirateruna, Efendi S; Habibi, Anang (International Journal of Artificial Intelligence & Robotics (IJAIR), 2024)
In recent years, electricity consumption in Indonesia rose to 1.109 kWh, as the Ministry of Energy and Mineral Resources reported. An alternate method for generating electrical energy is harvesting the energy produced via exercising on a stationary bike. By employing Arduino Mega 2560pro-powered torque control using the PID (Proportional – Integral – Derivative) technique, we can effectively save the generator's power in the battery and modify the paddle load to match the user's desired settings. The design incorporates a repurposed bicycle that has been rebuilt, along with the addition of a transmission gear, a controller box housing a control circuit, a relay, and an inverter. Additionally, it is equipped with a display and buttons. This system can generate a paddle load ranging from 1 to 17 in normal mode and 1 to 10 in PID mode. The system has a maximum current output of 3.2A and a battery capacity of 24VDC. This DC voltage is then transformed into a 220 VA AC voltage suitable for residential electrical use using an inverter. The PID controller will regulate the current flowing into the battery, ensuring it remains steady even with a consistent wood load. PID control can reach a set point at the settling time, 7 s, with an overshoot and a steady-state error of 0%. Every motor achieved the Pulse Width Modulation (PWM) value set to the ideal current. As the RPM increases, the PWM decreases until it reaches the preset set point with a constant current value.